PERAN ORANGTUA ASUH DALAM MENINGKATKAN KREATIVITAS ANAK PANTI MELALUI PELATIHAN DI PANTI ASUHAN YATIM PUTRI BHAKTI IBU LUBUK SIKAPING - Afrina Afrina; Linda Yarni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Foster parents play an important role in exploring and developing the creative potential of foster children. Foster parents play a very important role in motivating children, as well as directing the activities of foster children so that they are useful in the future. One of them is motivating and directing children to participate in creativity development activities in the form of handicrafts. Creativity is an important thing in a person's life because it can make a person more productive and improve the quality of life and make it easier to find a way out of a problem. Through children's orphanages with various activities that are able to develop themselves both physically and spiritually. Orphanages can also form children's personalities to become independent and accustomed to things that train children to be more perfect. The purpose of this study was to determine the role of foster parents in developing the creativity of orphanage children through training. This study used a qualitative approach with descriptive methods and data obtained through observation and interviews. The location of this research is located at the Yatim Putri Bhakti Orphanage, Ms. Lubuk Attitude. With this research, it can be seen that the role of foster parents in increasing the creativity of orphans through training at the Yatim Putri Bhakti Orphanage, Mrs. Lubuk Kapaning, is by providing handicraft training, orphanage children can develop their creativity and become independent.